Typology and spatial patterns of warehousing in Cape Town, South Africa - Garatsa, Francis (Cape Peninsula University of Technology, 2024)
As a result of globalisation and e-commerce, the freight flows have dramatically increased in metropolitan areas, contributing significantly to changes in the spatial location of logistics facilities generally and warehouses specifically. Warehouses are pertinent for spatial planning because they are land-intensive and big generators of freight traffic. There is however sparse literature on the spatial patterns of different warehousing types. The understanding of warehouse types would enable policymakers and planners to differentiate warehousing facilities and their locational needs since warehousing facilities vary in terms of size, resulting in some facilities consuming large parcels of urban land. The aim of the study was to analyse the spatial patterns of warehousing types and draw implications for spatial planning. The study answered the following research questions: What factors influence the spatial pattern of warehousing typologies? and How are the different typologies of warehousing facilities spatially distributed in the City of Cape Town municipality? The study adopted a case study approach, focusing on the City of Cape Town as defined by the administrative municipal boundary, and further classified into ten districts. The study used the building size/ footprint criterion to classify warehouses. Hinging on the descriptive quantitative approach, the geospatial data on the spatial distribution of warehousing was obtained from AfriGIS. Footprint analysis was then used to analyse the building size of warehouse facilities across the City of Cape Town. The study found that the majority of the warehouses in the City of Cape Town were x-small, followed by small, medium and large warehouses, while xx-small, x-large and mega warehouses accounted for the same number. Table Bay District accommodated the largest number of warehouses, with diverse typologies, while the Southern District accommodated the least number. Warehouses were located close to the main traffic corridors, the railway line, the airport and seaport. In terms of zoning, the study found that the highest concentration of warehouses in the general industrial zones. The study recommends that the municipality consider planning for different typologies of warehouses.
Thesis (Master of Urban and Regional Planning)--Cape Peninsula University of Technology, 2024
Keywords: Warehouses -- Location; Spatial analysis (Statistics); Typology; Business logistics; Geographic information systems; City planning